ChemInform Abstract: Gold‐Catalyzed Cyclization Processes: Pivotal Avenues for Organic Synthesis. Issue 16 (March 2016) - Kumar, Amit; Singh, Sukhdev; Sharma, Sunil K.; Parmar, Virinder S.; Van der Eycken, Erik V.
Abstract: Review: [52 refs.